Community awareness on dengue and practices of mosquito bite prevention in urban residents of a central Indian city, Sagar, Madhya Pradesh - Guleri, Sunil K.; Mahore, Rakesh K.; Panika, Ram K.; Rohit, Bhupendra K. (International Journal Of Community Medicine And Public Health, 2019)
Background: Dengue is an arboviral, mosquito borne illness caused by bite of infected aedes mosquitoes which breed commonly on household water containers like cooler tank, fridge trays and flower pots. Though dengue is non fatal illness but it may lead to deaths from dengue hemorrhagic fever and dengue shock syndrome. The objective of the study was to assess the community awareness regarding dengue and practices primarily being used as personal protection measures against mosquito bites and abolition of household breeding sites of mosquitoes. Methods: A cross sectional observational study done in 5 randomly selected wards of the municipal corporation Sagar. 400 households were studied, selecting 80 houses from each ward randomly. Pretested structured questionnaire was used for interview with the head of family/adult member of the family. The data collected was analysed using SPSS software and chi square test was applied as test of significance. Results: The households studied were mostly (28.2%) of lower middle class (modified B G Prasad scale). the dengue awareness in the community was fair (44.25%) and satisfactory (46.25) in Likert scale. Awareness regarding household breeding sites of mosquitoes was absolute (100%) but the use of personal protective measures was partial (50%). Conclusions: The knowledge and awareness to stop the mosquito breeding, biting should be enhanced and should be turned into action.